A Case Study on Perusahaan Otomobil Kedua Sdn. Bhd. – Establishment of One-Stop Integrated Center - Husin, Zahari (1999)
This is the case of strategic decision in marketing issue, particularly in Strategic Distribution System. The case background provided complete scenario of the potential threats to Perodua 's future and discussed in length the current and future effects of the deficiency in distribution facilities to Perodua overall operation. The case write-up also presented the proposed plan for the establishment of an Integrated Delivery Center (IDe) in Klang Valley. In the case analysis, several strategic tools were employed in order to evaluate the competitive position and direction for Perodua . The findings were used to analyze the possible problem(s) and propose best alternative solutions for Perodua to embark on. The analysis also provided various scale of action plan to be undertaken by Perodua in its effort to improve Perodua 's position and put Perodua in the proper direction in meeting the market challenges in the new millennium.